2021
DOI: 10.3390/en14154443
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Fungal Strains for Cellulolytic and Xylanolytic Activities Production and Evaluation of Brewers’ Spent Grain as Substrate for Enzyme Production by Selected Fungi

Abstract: Brewer’s spent grain (BSG), the solid residue of beer production, is attracting significant attention as raw material for the production of added value substances, since until recently it was mainly used as animal feed or deposited in landfills, causing serious environmental problems. Therefore, this work aimed at developing a bioprocess using BSG as a substrate for the production of cellulases and xylanases for waste saccharification and bioenergy production. Different fungi were analyzed for their cellulolyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…Cellulase activity was maximum at 50°C, but good activity levels were observed between 35°C and 65°C. Similarly, optimum cellulase activity was also observed at 50°C when fermenting raw oil palm leaves with Rhizopus oryzae ( Ezeilo et al, 2020 ), at 55°C for the cellulase produced by Trichoderma reesei ( Astolfi et al, 2019 ), and at 60°C for the cellulase produced by A. niger during the SSF of BSG ( Liguori et al, 2021 ).…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…Cellulase activity was maximum at 50°C, but good activity levels were observed between 35°C and 65°C. Similarly, optimum cellulase activity was also observed at 50°C when fermenting raw oil palm leaves with Rhizopus oryzae ( Ezeilo et al, 2020 ), at 55°C for the cellulase produced by Trichoderma reesei ( Astolfi et al, 2019 ), and at 60°C for the cellulase produced by A. niger during the SSF of BSG ( Liguori et al, 2021 ).…”
Section: Discussionmentioning
confidence: 89%
“…In the present study, the optimum temperature that maximizes xylanase activity was determined to range between 45°C and 65°C, with maximum activity at 55°C. Similarly, maximum activity of xylanase produced by Aspergillus flavus was attained at 55°C ( Chen et al, 2019 ), that of xylanase produced by Simplicilium obclavatum during the wheat bran SSF was attained at 50°C ( Roy et al, 2013 ), that of xylanase produced by Rhyzopus oryzae during the SSF of raw oil palm frond leaves was attained at 60°C ( Ezeilo et al, 2020 ), and that of xylanase produced by A. niger after 10 days of the SSF of BSG was attained at 50°C ( Liguori et al, 2021 ). However, other authors reported lower optimal temperatures for xylanase activity, such as that produced from Pediococcus acidilactici , showing maximum activity at 40°C ( Adiguzel et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Liguori et al . (2021) reported a value of 60 U mL −1 for xylanase activity in SSF from filamentous fungi strains of Penicillium occitanis SM6. Therefore, FG presented a highly effective enzymatic degradation of hemicelluloses through xylanase, which can improve food properties.…”
Section: Resultsmentioning
confidence: 99%